Dark secrets of childhood : media power, child abuse and public scandals - Powell, Fred W.; Scanlon, Margaret, 1965- (Bristol, UK : Policy Press, 2015)
This ground-breaking book explores the relationship between the media, child abuse and shifting adult-child power relations which, in Western countries, has spawned an ever-expanding range of laws, policies and procedures introduced to address the 'explosion' of interest in the issue of child abuse.
Title from publisher's bibliographic system (viewed on 11 Mar 2022).
Keywords: Child abuse -- Ireland; Child sexual abuse -- Investigation -- Ireland; Child sexual abuse in mass media